Translational issues for human corneal endothelial tissue engineering. (25th April 2016) - Soh, Yu Qiang; Peh, Gary S. L.; Mehta, Jodhbir S.
Abstract: Corneal endothelial disorders collectively represent a significant healthcare burden in most developed nations, and corneal transplantation is currently the only treatment available for patients with poor visual acuity and corneal blindness secondary to endothelial failure. Although vision in these patients can be restored by transplantation, the global demand for donor human corneas is far in excess of what can be provided for by eye banks around the world, and this deficit is set to increase with an ageing global population. As such, there has been a pressing need to explore novel and more sustainable options for the treatment of corneal endothelial diseases. In recent years, significant progress has been made not only in the development of corneal endothelial cell culture techniques, but also in the exploration of various translational strategies. Considered together, we are now much closer to attaining success in the treatment of corneal endothelial diseases via a cell‐based, tissue‐engineering approach. The aim of this review article is to provide an update of the translational issues currently facing human corneal endothelial cell therapy. Copyright © 2016 John Wiley & Sons, Ltd.